2020
DOI: 10.1177/1464420720981404
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metallic fiber geometry and multi-walled carbon nanotubes on the mechanical behavior of aluminum fiber-reinforced composite adhesive joints

Abstract: The effect of the geometry of metallic fibers on the mechanical response of aluminum fiber-reinforced composite adhesive joints was studied experimentally. Moreover, a combination of multi-walled carbon nanotubes and aluminum fibers was used for reinforcing the composite adhesive joints. Different geometries for the aluminum fibers including straight, twisted and spring-shaped with different pitch lengths were considered. The results indicated that the composite adhesive joints reinforced with a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They observed that, for 0.5 and 0.8 wt.% content, using a mixture of nano silica and MWCNT particles into the adhesive led to a higher shear strength compared with single‐type reinforcement by each particle. Khayamdar and Khoramishad 33 found that the hybrid incorporation of MWCNTs and aluminum fibers led to greatest enhancements in static strength of adhesive joints. In a study performed by Zamani et al, 34 the influence of separate and mixed addition of nano silica and GNP particles into an epoxy adhesive was investigated on the static strength, fatigue behavior, and fatigue crack initiation life (CIL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that, for 0.5 and 0.8 wt.% content, using a mixture of nano silica and MWCNT particles into the adhesive led to a higher shear strength compared with single‐type reinforcement by each particle. Khayamdar and Khoramishad 33 found that the hybrid incorporation of MWCNTs and aluminum fibers led to greatest enhancements in static strength of adhesive joints. In a study performed by Zamani et al, 34 the influence of separate and mixed addition of nano silica and GNP particles into an epoxy adhesive was investigated on the static strength, fatigue behavior, and fatigue crack initiation life (CIL).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, limited research studies have been performed on evaluating the mechanical behavior of bonded joints by hybrid insertion of nanoparticles 32–34 . Thus, it is important to study the scenario of hybrid nanoparticle reinforcement, including particles with different shapes and features, from the static and fatigue behavior aspects, and also from the microstructural point of view to reveal damage mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The design concept of carbon fiber and other innovative materials reinforced metal matrix composites (MMCs) provides new ideas for the development of new materials with excellent mechanical properties. Some studies have achieved remarkable results using carbon fiber-reinforced Al, Cu, and Mg- based MMCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was stated that the modulus of elasticity increased by 35% and the tensile strength increased by 44% with the GO nanoplatelets addition. In a study by Khayamdar et al, 18 the mechanical properties of the adhesive joints were investigated by adding aluminum fiber with different geometries and CNT into the adhesive. They concluded that the highest improvement in the strength of joints was achieved with a combination of CNT and aluminum fibers, and this value was 171% compared to the neat specimen.…”
Section: Introductionmentioning
confidence: 99%